The Battle of Konotop 1659 - Giovanna Brogi Bercoff; Oleg Rumyantsev (Ledizioni, 2012)
Exploring alternatives in East European history. The battle that took place near Konotop in late June 1659 was a continuation of the Muscovite-Cossack war, which began in the fall of 1658, soon after the signing of the Union of Hadiach. Cossack and Tatar detachments trapped a significant portion of the Muscovite army, leading to enormous Russian losses.
English